Dinamika pelaksanaan work from anywhere (WFA) - Basri, Nismawaty; Hanifah, Laily (Holistik Jurnal Kesehatan, 2026)
Background: The Industrial Revolution 4.0 and the post-COVID-19 pandemic are driving bureaucratic transformation through flexible work models such as Work from Anywhere (WFA). In Indonesia, this policy was adopted for the civil servants to modernize the bureaucracy and achieve budget efficiency. The Jakarta Health Training Center is a pioneer in implementing WFA within the Ministry of Health in 2025. Purpose: To identify the perceptions and experiences of civil servants, analyze the challenges, explore the benefits, and formulate policy recommendations related to WFA implementation. Method: This research used a qualitative case study approach. Data were collected through in-depth interviews with nine purposively selected informants, observation, and documentation. Data analysis was conducted using thematic analysis. Results: Findings indicate that civil servants have a positive perception of WFA because it increases flexibility and work-life balance. However, key challenges include internet network instability, obstacles to online coordination, and disruptions from the home environment. Trust-based leadership support is a key factor in successful implementation. Conclusion: Implementing WFA is a strategic step in digital transformation that effectively increases job satisfaction. However, this requires strengthening digital infrastructure, implementing an output-based performance evaluation system, and improving technological literacy for all civil servants.   Keywords: Civil Servants; Digital Transformation; Flexibility; Work Efficiency; Work from Anywhere (WFA).   Pendahuluan: Revolusi industri 4.0 dan pasca-pandemi COVID-19 mendorong transformasi birokrasi melalui model kerja fleksibel seperti Work from Anywhere (WFA). Di Indonesia, kebijakan ini diadopsi bagi Aparatur Sipil Negara (ASN) untuk modernisasi birokrasi dan efisiensi anggaran. Balai Besar Pelatihan Kesehatan (BBPK) Jakarta menjadi pionir implementasi WFA di lingkungan Kementerian Kesehatan pada tahun 2025. Tujuan: Untuk mengidentifikasi persepsi dan pengalaman ASN, menganalisis tantangan, menggali manfaat, serta merumuskan rekomendasi kebijakan terkait pelaksanaan WFA. Metode: Penelitian ini menggunakan pendekatan kualitatif dengan jenis studi kasus. Data dikumpulkan melalui wawancara mendalam terhadap 9 informan yang dipilih secara purposive, observasi, dan dokumentasi. Analisis data dilakukan dengan metode analisis tematik (thematic analysis). Hasil: Temuan menunjukkan, bahwa ASN memiliki persepsi positif terhadap WFA karena meningkatkan fleksibilitas dan keseimbangan kehidupan kerja. Namun, tantangan utama yang dihadapi meliputi ketidakstabilan jaringan internet, hambatan koordinasi daring, dan gangguan lingkungan rumah. Dukungan kepemimpinan yang berbasis kepercayaan menjadi faktor kunci keberhasilan implementasi. Simpulan: Pelaksanaan WFA merupakan langkah strategis transformasi digital yang efektif meningkatkan kepuasan kerja. Namun, memerlukan penguatan infrastruktur digital, sistem evaluasi kinerja berbasis hasil (output-based), dan peningkatan literasi teknologi bagi seluruh ASN. Kata Kunci: Aparatur Sipil Negara (ASN); Efisiensi Kerja; Fleksibilitas; Transformasi Digital; Work from Anywhere (WFA).